The blind spot: value‐based health care in obstetrics and gynaecology. (7th January 2022) - Naji, Osama; Souter, Vivienne; Mullins, Edward; Gaughran, Jonathan; Diab, Yasser; Fitzgerald, J Edward; Bourne, Tom; Morris, Edward
Abstract : Key content: Continuing financial constraints on the UK's National Health Service means the need for clinicians to provide high‐quality care in a cost‐effective way has never been greater. While the medical education system equips doctors with skills to provide safe clinical care, it should also provide an understanding of healthcare costs and cost‐effectiveness analysis. Value‐based care is becoming a key paradigm in women's health services, where clinicians must employ strategies for delivering value, rationalising costs and capitalising on the use of emerging technologies. The calculation of value of an intervention for providers and service users may differ; care must be taken to ensure this concept is adapted for, and not imposed on healthcare systems. Engaging trainees in systems transformation and embedding the concepts of 'do no financial harm' are essential to ensure sustainable healthcare services. Learning Objectives: To understand the principles of value‐based health care. To highlight the importance of adopting 'cost‐conscious' care within daily clinical practice. To learn the differences between 'cost', 'charge', 'price' and 'reimbursement. To encourage developing value‐based competencies for future medical workforce through utilising out of programme placements and digital resources. Ethical Issues: The ethical obligation of clinicians to consider cost may encompass justice and equity. However, the impact of practicing value‐based health care is yet to be evaluated.